2020
DOI: 10.1302/2046-3758.910.bjr-2020-0140.r1
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of miR-21-5p alleviates cartilage matrix degradation by targeting Gdf5 in temporomandibular joint osteoarthritis

Abstract: Aims The study aimed to determine whether the microRNA miR21-5p (MiR21) mediates temporomandibular joint osteoarthritis (TMJ-OA) by targeting growth differentiation factor 5 (Gdf5). Methods TMJ-OA was induced in MiR21 knockout (KO) mice and wild-type (WT) mice by a unilateral anterior crossbite (UAC) procedure. Mouse tissues exhibited histopathological changes, as assessed by: Safranin O, toluidine blue, and immunohistochemistry staining; western blotting (WB); and quantitative real-time polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…80 Researchers suggested that both miR‐101a‐3p and miR21-5p was involved in the cartilage matrix degradation as well as in progression of degenerative changes of TMJ. 81 …”
Section: Role Of Mirnas In Tmd Painmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Researchers suggested that both miR‐101a‐3p and miR21-5p was involved in the cartilage matrix degradation as well as in progression of degenerative changes of TMJ. 81 …”
Section: Role Of Mirnas In Tmd Painmentioning
confidence: 99%
“… Sato et al 71 Growth factors NGF and VEGF Plasma and Synovial Fluid Persistent pain and pain progression in TMD disc and degenerative joint diseases. Chen et al 74 , Ke et al 75 Epigenetic biomarkers (miRNA) Tissue: Synovial fibroblasts and articular cartilage Altered expression of miRNA221–3p, miRNA 140-5p, miR‐101a‐3p, miR21-5p were observed in DJD and Pain Zhang et al 81 , Li et al 79 , Xu et al 78 Neuroimaging biomarkers Structural MRI Decreased trigeminal nerve fiber density, axonal diameter, myelination and GMV correlated well with TMD pain in patients with TMJ synovitis and myofascial pain. Zhang et al 91 , Wilcox et al 87 , He et al 98 , Moayedi et al 88 , Gustin et al 89 , Weissman-Fogel et al 94 , Ichesco et al 92 , Younger et al 90 , Buckner et al 93 Functional MRI Alterations in FC, GMV CBF, MD was observed in different regions of high order cognition, emotion-related regions such as ACC, PCC, MCCC, mPFC, DLPFC, Amygdala, and PAG-raphe system.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 miRNAs have been shown to be closely related to the progression and severity of OA. 34,35 Therefore, the regulatory mechanism underlying circSCAPER in OA was further explored, and we confirmed that circSCAPER directly binds to miR-140-3p. miR-140-3p isomiRs are abundantly expressed in cartilage, which is more effective than the original miR-140-3p annotated in miRBase [36][37][38] in human and murine chondrocytes, 39 suggesting the potential function of miR-140-3p in OA.…”
Section: Discussionmentioning
confidence: 60%
“…MiR-21 inhibits the expression of GDF-5 and its overexpression attenuates the progression of OA ( Zhang et al, 2014 ). This finding was validated in the mouse temporomandibular joint osteoarthritis (TMJOA) model, where Zhang et al claimed that knockdown of miR-21-5p reduced cartilage matrix degradation in TMJOA by targeting GDF-5 ( Zhang A. et al, 2020 ). Also in the mouse TMJOA model, researchers discovered that miR-21-5p knockout mice had less temporomandibular joint cartilage destruction than wild-type mice, and in vitro experiments showed that miR-21-5p promotes extracellular matrix degradation and angiogenesis in TMJOA by suppressing the expression of target gene SPRY1, which in turn promotes the development of TMJOA ( Ma et al, 2020 ).…”
Section: The Regulatory Role Of Mir-21 In Oamentioning
confidence: 80%